Crystal-orientation-dependent corrosion behaviour of single crystals of a pure Mg and Mg-Al and Mg-Cu solid solutions. (August 2016) - Hagihara, Koji; Okubo, Masayoshi; Yamasaki, Michiaki; Nakano, Takayoshi
Highlights: Orientation-dependent corrosion behaviour of Mg single crystals was examined. Charge-transfer and film resistances exhibit strong orientation dependence. Variations in atomic packing density on the surface govern the behaviour. Adding Al predominantly affected the orientation dependence of the film resistance. Adding Cu decreased the orientation dependence of corrosion behaviour. Abstract: Mg alloys are promising candidates for biodegradable materials. To control their dissolution rate, the orientation-dependent corrosion behaviour of pure-Mg single crystals was examined. The corrosion rates increased in the order ( 0001 ) < ( 11 2 ¯ 0 ) < ( 10 1 ¯ 0 ) < ( 11 2 ¯ 3 ) < ( 10 1 ¯ 2 ) . We found the anodic reaction governs the orientation-dependent corrosion behaviour. The charge-transfer and film resistances were strongly orientation-dependent. Effects of Al or Cu-addition to the orientation-dependent corrosion behaviour were also examined as model materials. Al-addition promoted passivation in anodic polarization, while Cu-addition activated the cathodic reaction. However, neither Al nor Cu influenced the order of orientation-dependent corrosion behaviour. Such orientation-dependence may originate from the variation in surface atomic-packing density.